Comparison of the Journey II bicruciate stabilised (JII-BCS) and GENESIS II total knee arthroplasty for functional ability and motor impairment: the CAPAbility, blinded, randomised controlled trial - Allan B Clark; Toby O Smith; J Wells; Iain McNamara; Juliet High; Ann Marie Swart; Valerie Pomeroy; Graham Creelman; Celia Whitehouse; B Harry; Celia Clarke (BMJ Open)
Objectives To determine if a newer design of total knee replacement (TKR) (Journey II BCS) produces superior patient-reported outcomes scores and biomechanical outcomes than the older, more established design (Genesis II).Setting Patients were recruited from an NHS University Hospital between July 2018 and October 2019 with surgery at two sites. Biomechanical and functional capacity measurements were at a University Movement and Exercise Laboratory.Participants 80 participants undergoing single-stage TKR.Interventions Patients were randomised to receive either the Journey II BCS (JII-BCS) or Genesis II TKR.Primary and secondary outcome measures Primary outcome was the Oxford Knee Score (OKS), at 6 months. Secondary outcomes were: OKS Activity and Participation Questionnaire, EQ-5D-5L and UCLA Activity scores, Timed Up and Go Test, 6 min walk test, lower limb kinematics and lower limb muscle activity during walking and balance.Results This study found no difference in the OKS between groups. The OKS scores for the JII-BCS and Genesis II groups were mean (SD) 42.97 (5.21) and 43.13 (5.20) respectively, adjusted effect size 0.35 (-2.01,2.71) p=0.771In secondary outcome measures, the Genesis II group demonstrated a significantly greater walking range-of-movement (50.62 (7.33) vs 46.07 (7.71) degrees, adjusted effect size, 3.14 (0.61,5.68) p=0.02) and higher peak knee flexion angular velocity during walking (mean (SD) 307.69 (38.96) vs 330.38 (41.40) degrees/second, adjusted effect size was 21.75 (4.54,38.96), p=0.01) and better postural control (smaller resultant centre of path length) during quiet standing than the JII-BCS group (mean (SD) 158.14 (65.40) vs 235.48 (176.94) mm, adjusted effect size, 59.91 (–105.98, –13.85) p=0.01.).Conclusions In this study population, the findings do not support the hypothesis that the Journey II BCS produces a better outcome than the Genesis II for the primary outcome of the OKS at 6 months after surgery.Trial registration number ISRCTN32315753.